PENGARUH INSENTIF DAN MOTIVASI TERHADAP KINERJA KARYAWAN BUCCHERI DI SAMARINDA - Dwi Sampurni, Aprilia; Riduansah, Riduansah (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
The aim of this research is to determine the influence of incentives and motivation on the performance of Buccheri employees in Samarinda. This type of research is quantitative research with a sample of 35 respondents. Primary data uses a questionnaire in the form of statements with a Likert scale which is distributed to Buccheri employees using Google Form. Data analysis collection tools use multiple linear regression tests, but instrument tests use multiple regression tests, partial correlation tests (r), coefficient of determination tests, Classical Assumption Tests. The hypothesis test uses the t test and F test with SPSS tools. The research results show that the incentive variable (X1) has a significant effect on employee performance at Buccheri Samarinda. the first hypothesis is accepted. Then the motivation variable (X2) has a significant effect on employee performance at Buccheri Samarinda, the second hypothesis is accepted and the incentive and motivation variables simultaneously (simultaneously) influence the performance of Buccheri employees in Samarinda, the third hypothesis is accepted. The influence that the incentive and motivation variables together have on employee performance is 51.5%, while 48.5% is influenced by other factors